The manganese efflux system MntE contributes to the virulence of Streptococcus suis serotype 2. (September 2017) - Xu, Jiali; Zheng, Chengkun; Cao, Manman; Zeng, Ting; Zhao, Xigong; Shi, Guolin; Chen, Huanchun; Bei, Weicheng
Abstract: Manganese is an essential micronutrient to bacteria and plays an important role in bacterial physiology. However, an excess of manganese is extremely deleterious to the cell. The manganese efflux system is used to control intracellular manganese levels by some bacteria. In this study, we have identified a cation efflux family protein (MntE) that functions as a manganese export system in Streptococcus suis serotype 2. To investigate the role of mntE in S. suis 2, a mntE deletion mutant ( ΔmntE ) and the corresponding complementation strain (C ΔmntE ) were constructed. ΔmntE displayed similar growth compared to the wild-type and complementation strains under normal growth conditions, but was defective in medium supplemented with high concentrations of manganese. In addition, the mutant was more sensitive to oxidative stress conferred by diamide. Using a competitive-infection assay in the murine infection model, we demonstrated for the first time that MntE is involved in the virulence of S. suis 2. Collectively, our data indicate that manganese homeostasis controlled by the manganese efflux system MntE is important for the pathogenesis of S. suis 2. Highlights: MntE functions as a manganese efflux system in S. suis 2. MntE is involved in tolerance to oxidative stress conferred by diamide. The virulence of ΔmntE is attenuated in the murine infection model.